From waste to health: exploring the male sexuality enhancing activities of the bioactive components of orange peel - Odetayo, Adeyemi Fatai; Bassey, Grace Edet; Adeyemi, Adenike Lizzy; Olayaki, Luqman Aribidesi (Frontiers in Endocrinology, 2025)
Large amounts of citrus wastes, especially orange peels, are produced globally, and they are an environmental menace in different parts of the world because of their perishability. However, various research findings have shown that orange peels are a rich source of vitamins, fibers, phenols, and other bioactive compounds. This makes orange peel a promising therapeutic option for managing various disease conditions. Despite these health benefits, only about 10% of orange peel produced as waste is recycled and reused. Hence, the review was designed to explore the beneficial roles of orange peel bioactive compounds on male sexual function. This review, therefore, explore the aphrodisiac effect of orange peel bioactive compounds by reviewing recent publications that detail the association of orange peel bioactive compounds with male sexual functions regarding its potential roles in erectile function regulation, testosterone levels, and semen characteristics. Bioactive compounds from orange peel contributed positively to sexual and erectile functions. This was mediated via a hormonal-dependent mechanism and upregulation of steroidogenic enzymatic activities. It also improves endothelial functions by stimulating the secretion and release of nitric oxide, which is important for erection. Furthermore, it acts by mediating the activities of monoamine neurotransmitters, which are responsible for the motor activities involved in sexual function. Orange peel bioactive compounds enhance male sexual functions via multiple pathways. Hence, orange peels offer great potential for developing functional food products with health and economic benefits.